2019
DOI: 10.3390/en12163136
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Temperature, Moisture and Electric Field on the Electrical Conductivity of Oil-Impregnated Pressboard

Abstract: The main insulation of converter transformers consists of transformer oil and oil-impregnated pressboard. Under operating conditions, the valve-side winding of the converter transformer is subject to DC voltage components. Therefore, studies on the characteristics of oil-impregnated pressboard conductivity are necessary. In this paper, the temperature, moisture and electric field dependency of pressboard conductivity are investigated based on a specially designed three-electrode experimental chamber, which all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The increase in moisture has a number of negative consequences that are important for the transformer insulation system, but also for its other elements. First of all, reducing the resistivity of insulation materials [31] and the breakdown voltage [32,33] belong to the most important of them. As a consequence, this may lead to a decrease in the initial voltage of partial discharges [30], thus contributing to an increase in the likelihood of an unexpected transformer failure [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in moisture has a number of negative consequences that are important for the transformer insulation system, but also for its other elements. First of all, reducing the resistivity of insulation materials [31] and the breakdown voltage [32,33] belong to the most important of them. As a consequence, this may lead to a decrease in the initial voltage of partial discharges [30], thus contributing to an increase in the likelihood of an unexpected transformer failure [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Although in case of mineral oil, the conductivity data for high voltage DC applications are already given in literature [52,76,102,103], the measurements have been done to support a reliable design of the measuring system. The measured conductivity values, which are also summarized in Table 3-1, strongly depend on temperature, and a weak dependency to the electric stress can be observed as well.…”
Section: Mineral Oil and Oipmentioning
confidence: 99%
“…Oil impregnated pressboard is the primary insulating material used in converter transformers, where it has to bear significant DC stresses. It has been experimentally observed that the DC conductivity of oil-pressboard insulation increases with applied electric stress [1][2]. However, little is known about the conduction mechanism responsible for such behaviour even though the value of DC conductivity becomes very important during the calculation of electric field distribution under HVDC environment [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In these investigations it was observed that charge density increases significantly with the enhancement of external field. Some recent investigations [1][2] focused on the effect of temperature on the conductivity of oil-pressboard. However, the physical mechanisms responsible for conduction process were not investigated.…”
Section: Introductionmentioning
confidence: 99%